The role of digital transformation in administrative reform in Lattakia Education Directorate (Journal of Hama University, 2024)
The aim of the research is to study the role of digital transformation in the administrative reform process in the Lattakia Education Directorate. The researcher took four dimensions of digital transformation: (source of value, basic activities, cost structure, and main resources For the purpose of conducting the study, the researcher followed the descriptive approach, where the researcher conducted the study using a questionnaire in the Directorate of Education of Lattakia and some educational complexes affiliated to it, which was organized based on previous literature in addition to secondary and primary data. 135 questionnaires were distributed, all of which were recovered, and the validity for analysis was 134. The SPSS program (20) was used to analyze the data, and a number of results were reached, the most important of which is that digital transformation technology works to develop and increase expertise in the areas of administrative reform. The use of digital transformation contributes to achieving higher vision and performance. Then, increasing customer expectations regarding the quality of services provided to them, the delivery process, presenting offers, and new business models. It became clear that digital transformation technology works effectively to improve productivity and encourage workers and managers to do new work.
Keywords: Digital transformation, administrative reform, Latakia Education Directorate